THE CONTENT OF PEDAGOGICAL DISCIPLINES AIMED AT CONTINUOUS DIDACTICAL TRAINING OF UNIVERSITY STUDENTS - Kadirova Munira Rasulovna; Akramjonova Nargiza Dilshodovna (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2021)
The content of pedagogical disciplines aimed at intensifying didactic training is analyzed. The methodology for intensifying the didactic training of future bachelor teachers has been substantiated.